New and newly recorded species of Psathyrella (Psathyrellaceae, Agaricales) from northeast China - Yan, Jun-Qing; Bau, Tolgor (Phytotaxa, 2017)
Four species of Psathyrella—P. subspadiceogrisea sp. nov., P. boreifasciculata, P. gordonii, P. senex were discovered in northeast China. P. subspadiceogrisea is described as new from Changbai Mountain; the other three species are recorded in China for the first time. The specimens were identified based on morphological characteristics and molecular analysis of ITS sequences. Detailed morphological descriptions, line drawings and photographs are presented.